Addressing the use of PDIF-CN2 molecules in the development of n-type organic field-effect transistors for biosensing applications - Barra, M.; Viggiano, D.; Ambrosino, P.; Bloisi, F.; Di Girolamo, F.V.; Soldovieri, M.V.; Taglialatela, M.; Cassinese, A. (Biochimica et biophysica acta, 2013)
There is no doubt that future discoveries in the field of biochemistry will depend on the implementation of novel biosensing techniques, able to record biophysiological events with minimal biological interference. In this respect, organic electronics may represent an important new tool for the analysis of structures ranging from single molecules up to cellular events. Specifically, organic field-effect transistors (OFET) are potentially powerful devices for the real-time detection/transduction of bio-signals. Despite this interest, up to date, the experimental data useful to support the development of OFET-based biosensors are still few and, in particular, n-type (electron-transporting) devices, being fundamental to develop highly-performing circuits, have been scarcely investigated. Here, films of N,N′-1H,1H-perfluorobutyldicyanoperylene-carboxydi-imide (PDIF-CN2) molecules, a recently-introduced and very promising n-type semiconductor, have been evaporated on glass and silicon dioxide substrates to test the biocompatibility of this compound and its capability to stay electrically-active even in liquid environments. We found that PDIF-CN2 transistors can work steadily in water for several hours. Biocompatibility tests, based on in-vitro cell cultivation, remark the need to functionalize the PDIF-CN2 hydrophobic surface by extra-coating layers (i.e. poly-l-lysine) to favor the growth of confluent cellular populations. Our experimental data demonstrate that PDIF-CN2 compound is an interesting organic semiconductor to develop electronic devices to be used in the biological field. This work contributes to define a possible strategy for the fabrication of low-cost and flexible biosensors, based on complex organic complementary metal-oxide-semiconductor (CMOS) circuitry including both p- (hole-transporting) and n-type transistors. This article is part of a Special Issue entitled Organic Bioelectronics—Novel Applications in Biomedicine. ► Low-voltage n-type organic PDIF-CN2 transistors have been fabricated. ► Their electrical operation stability was investigated in liquid environments. ► Cell adhesion properties of PDIF-CN2 films are analyzed by using CHO cells. ► PDIF-CN2 films have been bio-functionalized by poly-l-lysine.